NARL Animal Research Facility. Annual Report for FY78. - Laursen ,Gary A; Selby,George M (1978)
The NARL Animal Research Facility is completing its fourth year of support from the Office of Naval Research Biophysics Program. The Animal Research Facility has provided scientists with unique opportunities to study northern animals maintained in an arctic environment. The Research animals live year round in outdoor cages where they are subjected to the temperature and light conditions found only in the arctic. This report documents the activities and accomplishments of the facility during FY78. (Author)